Theory and validation of optical transmission scanning for quantitative NDE of impact damage in GFRP composites. (15th December 2016) - Khomenko, Anton; Karpenko, Oleksii; Koricho, Ermias; Haq, Mahmoodul; Cloud, Gary L.; Udpa, Lalita
Abstract: Non-destructive evaluation (NDE) techniques that can measure both surface and subsurface defects are of critical importance in evaluating the integrity of GFRP composites. In the present work, optical transmission scanning (OTS) technique was proposed for acquiring high-resolution, rapid, and non-contact OT (optical transmittance)-scans of pristine and impacted GFRP samples. Advanced data analysis was developed and implemented to identify the number of delaminations at every scan position. The results agreed very well with the actual number and extent of delaminations observed directly from a cross-section of the specimen. Overall, the presented technique lays the groundwork for cost-effective, non-contact, rapid, and quantitative NDE of GFRP composite structures.